"Breaking the ice" - Poeplau, Christopher (Thünen Institute of Climate-Smart Agriculture, 2022)
Effects of land use change on soil carbon dynamics in subarctic soils were recorded • The interaction with the occurrence of permafrost under forest was the main focus • Greater carbon losses when forest soils were permanently frozen prior to change • Microbial carbon use efficiency improved with agricultural use